2003
DOI: 10.3732/ajb.90.11.1585
|View full text |Cite
|
Sign up to set email alerts
|

The Enigmatic Paleozoic plants Spermopteris and Phasmatocycas reconsidered

Abstract: Ovule-bearing leaves from the Paleozoic of North America assigned to Spermopteris and Phasmatocycas have been interpreted as primitive cycad megasporophylls. According to this hypothesis, Cycas megasporophylls were derived from a Spermopteris-like ancestor via Phasmatocycas and various other taeniopterid forms. This putative transformation entailed the phyletic shift of ovule attachment from the abaxial lamina surface of Spermopteris to the leaf midrib in Phasmatocyas. However, reexamination of the original Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Cycads are dioecious and long-lived plants. They have experienced a long process of evolution (Gao and Thomas, 1989; Axsmith et al, 2003) and should own high genetic diversity. However, a recent research proposed that the extant cycads evolved recently (Nagalingum et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Cycads are dioecious and long-lived plants. They have experienced a long process of evolution (Gao and Thomas, 1989; Axsmith et al, 2003) and should own high genetic diversity. However, a recent research proposed that the extant cycads evolved recently (Nagalingum et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Fossil evidence shows that cycads originated approximately 275–300 million years ago [10,11]. Molecular evidence also shows that cycads originated much earlier than flowering plants [12,13], which originated approximately 125 million years ago [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…These features can be seen clearly on the specimen, even though details of venation cannot be determined. Axsmith et al (2003) have reexamined specimens of this genus and have concluded that its cycad affinities are problematic. Phasmatocycas has been associated with Taeniopteris sterile foliage, which has not been identified in our collections from New Mexico.…”
Section: Cf Phasmatocycas Kansanus Mamaymentioning
confidence: 99%